# Functions QuestionWatch

#1

If f(x) is even and g(x) is odd, prove that fg(x) is even. [2 marks]
0
quote
8 years ago
#2
fg(-x) = f(g(-x)) = ...
0
quote
8 years ago
#3
Start by saying f(x)=2x and g(x)= 2x + 1
Then go on from there
0
quote
#4
(Original post by sonofdot)
fg(-x) = f(g(-x)) = ...
Ok, fg(-x) = f(g(-x)) = f(-g(x)) = ... then what?
0
quote
8 years ago
#5
(Original post by toby_ling)
Ok, fg(-x) = f(g(-x)) = f(-g(x)) = ... then what?
Let g(x) = y. Compare f(-y) and f(y)...
0
quote
8 years ago
#6
(Original post by brodiebro)
Start by saying f(x)=2x and g(x)= 2x + 1
Then go on from there
I think you've misunderstood 'even' and 'odd' in this context.
0
quote
X

new posts
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### University open days

• University of East Anglia (UEA)
Could you inspire the next generation? Find out more about becoming a Secondary teacher with UEA… Postgraduate
Thu, 18 Oct '18
• University of Warwick
Sat, 20 Oct '18
• University of Sheffield
Sat, 20 Oct '18

### Poll

Join the discussion

#### Who is most responsible for your success at university

Mostly me (475)
91.7%
Mostly my university including my lecturers/tutors (43)
8.3%